A Comparative Study between Peptic Ulcer Perforation Score, Mannheim Peritonitis Index, ASA Score, and Jabalpur Score in Predicting the Mortality in Perforated Peptic Ulcers - Koranne, Aboli; Byakodi, K G.; Teggimani, Vasant; Kamat, Vijay V.; Hiregoudar, Abhijith (The Surgery Journal, 2022)
Introduction Peptic ulcer disease continues to be a major public health in most developing countries despite the advances in medical management. The incidence of perforations remains high and has the highest mortality rate of any complication of ulcer disease. Risk stratification of cases will lead to better preoperative management and efficient utilization of intensive care unit resources. The purpose of the present study is to compare different existing scoring systems and identify the most accurate predictor of mortality in perforated peptic ulcer (PPU) cases.Materials and Methods This is an observational study conducted in Karnataka Institute of Medical Sciences, Hubli, India. All cases of PPU disease admitted from December 2017 to August 2019 who were treated surgically were included in the study. Demographic data were collected and peptic ulcer perforation (PULP) score, Mannheim peritonitis index (MPI), American Society of Anesthesiologists (ASA) score, and Jabalpur score (JS) were calculated for individual patient and compared. The patient was followed up during the postoperative period.Observation A total of 45 patients were included in the study with a mean age of 42.5 years. Most of the patients presented with 24 hours of the onset of symptoms. Nonsteroidal anti-inflammatory drug use was noted in 8.9% patients, and steroid use was present in 2.2% patients. Of the 45 patients, 7 deaths were reported. Between the various scoring systems, the MPI and JS were better predictors of mortality with a p-value of <0.001 and 0.007, respectively. In contrast, the PULP and ASA scores had p-value not statistically significant. However, the PULP score was a better predictor of postoperative complication with a p-value of 0.047.Conclusion Of the four scoring systems validated, the MPI and JS were better predictors of mortality in the given population. PULP score is a better predictor of postoperative complications in the present study.
Keywords: perforated peptic ulcer; mortality; peptic ulcer perforation score; Mannheim peritonitis index; Jabalpur score; American Society of Anesthesiologists score